Stroke 2019 Excellence in Diagnosis and Care. - Coplin, Leslie (Relias LLC, 2019)
Offering the latest updates in stroke research, Stroke 2019: Excellence in Diagnosis and Care, is an unbiased online CME/CE resource written and edited by leading clinical experts. This concise digital resource offers all the Joint Commission-required stroke credits (8 CME/CE) with per-module testing.